Expanding the phenotype of STRA6‐related disorder to include left ventricular non‐compaction. Issue 9 (29th June 2020) - Sun, Hairui; Yu, Shaomei; Zhou, Xiaoxue; Han, Lu; Zhang, Hongjia; He, Yihua
Abstract: Background: Syndromic microphthalmia‐9 (MCOPS9) is a rare autosomal recessive disorder caused by mutations in STRA6, an important regulator of vitamin A and retinoic acid metabolism. This disorder is characterized by bilateral clinical anophthalmia, pulmonary hypoplasia/aplasia, cardiac malformations, and diaphragmatic defects. The clinical characteristics of this disorder have not been fully determined because of the rarity of clinical reports. Methods: A comprehensive genotyping examination including copy number variation sequencing (CNV‐Seq) and whole‐exome sequencing (WES) was applied to a fetus of Han Chinese with bilateral anophthalmia, bilateral pulmonary agenesis, interrupted aortic arch type A, and left ventricular non‐compaction (LVNC). Results: No aneuploidy or pathogenic CNV were identified by CNV‐seq. WES analysis revealed a previously reported homozygous splice site (NM_022369.4:c.113+3_113+4del) in the STRA6 gene. This variant was confirmed by Sanger sequencing. The diagnosis of MCOPS9 was confirmed given the identification of the STRA6 mutation and the association of bilateral anophthalmia, pulmonary agenesis, and cardiac malformations. Conclusion: This case adds to the phenotypic spectrum of MCOPS9, supporting the association with LVNC, and the presence of interruption of aortic arch further demonstrates the variability of the cardiac malformations. Abstract : We describe a fetus with bilateral anophthalmia, bilateral pulmonary agenesis, interrupted aortic arch type A and left ventricular non‐compaction (LVNC) who was found to have a homozygous splicing variant in the STRA6 gene. This case adds to the phenotypic spectrum of STRA6‐related disorder, supports the association with LVNC, and suggests that the mutation herein reported may be a hotspot in STRA6.